Analisis Praktik Giveaway dalam Jual Beli Online pada Perspektif Ekonomi Syariah: Studi pada Oflaila_Busana - Hasibuan, Jahro; Edy, Sarwo; Ainulyaqin, MH. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to find out the giveaway practices carried out by oflaila_busana by buying and selling online from a sharia economic perspective. Currently, the practice of giveaway is widely used by online shops as a sales attraction, so that their products are better known by the wider community. This study uses a qualitative descriptive method by providing explanations and descriptions regarding giveaway buying and selling in the perspective of Islamic economics. Which is done by describing a problem or phenomenon that occurs accurately. And the results obtained are well described. Methods of data collection by means of observation, interviews, and/or document review. The research location is oflaila_busana which uses online media in sales by practicing a giveaway system in sales promotion. The results of this study based on the data obtained indicate that the giveaway held at oflaila_busana does not contain conditions that are prohibited in religion. So the giveaway practice at oflaila_busana is in accordance with the sharia economy.